The significance of markers in the diagnosis of endometrial cancer - Żyła, Monika M.; R. Wilczyński, Jacek; Kostrzewa, Marta; Księżakowska-Łakoma, Kinga; Nowak, Marek; Stachowiak, Grzegorz; Szyłło, Krzysztof; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2016)
Endometrial cancer is one of the most common cancers experienced by women throughout the world. It is also the most common malignancy within the female reproductive system, representing 37.7% of all disorders. The incidence increases with age, and is diagnosed most frequently in women between 45 and 65 years old. In the last few years, numerous studies have been performed to identify tumour biomarkers. Biomarkers include not only protein routinely used as tumour markers but also genes and chromosomes. The limiting factor in the use of markers in the diagnosis of endometrial cancer is their lack of specificity. However, specific markers for endometrial cancer are the subject of much research attention. Although moderately elevated levels of markers are present in a number of inflammatory or non-malignant diseases, significantly increased levels of markers indicate the development of cancer. Recently, research has been focused on the identification of molecular changes leading to different histological subtypes of endometrial cancer. In this paper the authors reviewed several currently investigated markers. Progress in these investigations is very important in the diagnostics and treatment of endometrial cancer. In particular, the identification of novel mutations and molecular profiles should enhance our ability to personalise adjuvant treatment with genome-guided targeted therapy.